Diluted Liquid Dishwashing Soap Effectively Displace Xylol in The Deparaffinization Process of Hematoxylin Eosin Staining - Lianita, Viona; Burhannudin, Burhannudin (Fakultas Kedokteran Universitas Riau, 2025)
This study aimed to determine the optimal concentration of Liquid dishwashing soap (LDS) in the deparaffinization process. The study analyzed 27FFPE of liver from Wistar rats (Rattus norvegicus) divided into three groups. Xylol as a control (C), LDS concentrations of 1.7% (P1) and 2% (P2) as treatments. The quality of hematoxylin Eosin staining results was evaluated using scoring, analyzed using Kruskal-Wallis and Mann-Whitney statistical tests (SPSS 26.0). The results showed a significant difference between xylol and 2% LDS concentration but no significant difference with 1.7% LDS concentration. Surfactant bind tightly with both water and paraffin to dissolve paraffin out. However, the lower viscosity solution made pulling paraffin inside the tissue easier. The study found that a lower concentration of LDS (1.7%) was more effective than a higher concentration (2%) in removing paraffin from tissue samples. Therefore, it is recommended to use 1.7% LDS as an alternative deparaffinization agent to xylol.